A Bilingual Immersive Environment for Kids Learning - Tufail Ahmad; Arifa Bibi; Umar Farooq; Ihsan Rabbi (Journal of Informatics and Web Engineering)
Virtual Worlds (VWs) provide an improved learning experience as they have an increased level of user participation and technological involvement. They avoid content duplication and following a set of predefined rules to overcome the issues in game environments. VWs are coherent, persistent and collaborative social places that believe in realism through immersion. Client viewer software is used for user immersion in the form of avatars and in-world content creation in these environments. This work presents a simple bi-lingual environment developed for kids’ learning in English and Urdu using the well-known VW development framework called OpenSimulator (OpSim). It used Firestorm viewer for in-world content development and Linden Scripting Language for making the content dynamic and interactive. This work used Blender, Adobe Photoshop and Illustrator for developing images of different objects and adding their related dynamics before integrating them within the OpSim. It developed some basic activities for learning about colours, national personalities of Pakistan, Urdu alphabets, geometrical shapes and fruits. Bots were used to populate the content for making it more appealing. The proposed environment provides an arbitrary number of tries to perform each activity and guides kids through a real time positive feedback towards an improved learning. This work conducted initial validation tests of the proposed presence on standalone mode of OpSim framework with the help of domain experts, which confirmed the effectiveness of the proposed mechanism. However, it was suggested to conduct further validation on grid mode of OpSim framework. The developed environment shall be compared with other methods for learning purposes. It could incorporate more languages, activities and lessons. 3D working models of the alphabets, fruits and vegetables, and customized avatars capable of interacting with kids would offer more positive impact on learning. Similarly, the simple tasks could be extended to multiplayer collaborative games.